State of the Art of Desalination in Mexico - Juan Ríos-Arriola; Nicolás Velázquez; Jesús Armando Aguilar-Jiménez; Germán Eduardo Dévora-Isiordia; Cristian Ascención Cásares-de la Torre; José Armando Corona-Sánchez; Saúl Islas (Energies, 2022)
This research paper presents a review of the state of the art of desalination in Mexico, with the aim of clarifying the main challenges and opportunity areas for desalination as the main solution to overcome water stress. First, the current situation and forecasts on the availability of water resources in Mexico are described, followed by the main economic, social, and legislative issues of desalination. Mexico’s installed capacity for the different desalination technologies and their evolution in recent years was investigated, followed by a comparison with global trends. The current state of research and development in desalination technologies carried out by Mexican institutions was also studied. The results show that membrane technology plants account for 88.85%, while thermal technology plants account for the remaining 11.15%. Although Mexico presented a 240% increase in its desalination capacity in the last 10 years, it has not been enough to overcome water stress, so it is concluded that in the future, it is necessary to increase its capacity in greater proportion, specifically in the areas with greater scarcity, which can be achieved with the joint participation of academy–industry–government through the creation of autonomous organizations, social programs, and/or public policies that promote it.